Synthesis, Crystal Structure, and Properties of a New Coordination Polymer From 4-(4-Hydroxypyridinium-1-yl) Phthalic Acid. Issue 10 (2nd October 2016) - Li, Fu-An; Li, Song-Tian; Yang, Wei-Chun
Abstract : A copper supramolecular coordination polymer, [CuL(H2 O)2 ]2 n (1 ), has been hydrothermally synthesized and structurally characterized by IR, UV spectroscopy, and elemental analyses, and also by single-crystal X-ray diffraction (H2 L = 4-(4-hydroxypyridinium-1-yl) phthalic acid). The coordination around Cu center is distorted octahedron coordination geometry involving six O atoms, and each L 2– ligand links three center atoms in the μ3- η 1 : η 1 : η 1 mode; Adjacent Cu(II) atoms are united by the monodentate carboxylate group and hydroxy group to form infinite 1D chains (···Cu1LCu2L···)n, which are further linked by coordinated bonds between Cu1 and chelating carboxylate groups to produce 2D layers. These 2D layers are extended by interlayer hydrogen-bonded interactions to form 3D supramolecular framework.